(untitled) - Harrower, Scott D. (U.S.A, 2019)
Surveying scripture, church history, and theology, sixteen contributors present a defense of the full and equal authority and majesty of all three members of the Trinity while critiquing approaches that border on semi-Arianism. Readers will learn why the strong statement of the equality of the Father and Son made at the council of Nicaea is necessary for a biblical and evangelical faith, having significant impact on our doctrine of God and the person of Christ. While some contributors hold complementarian and some egalitarian viewpoints, all agree that gender roles are not a proper basis for understanding Trinitarian relationships.
Keywords: Trinity